Principales acciones en la mitigación del cambio climático derivado de la producción pecuaria - Andrade Aguiar, Melany Katherine (2021)
Livestock production in the course of history became a fundamental means to meet nutritional needs and especially the animal protein requirements essential for the life and evolution of humanity, technological advances and the growing demand for products derived from livestock production and specifically ruminants, which for that matter are animals that, due to their nutritional and metabolic characteristics, produce residual gases, which become a very serious problem for humanity due to the negative changes produced when transforming a An indispensable condition for life such as the greenhouse effect. The problems that result from this situation have determined a climate change that has become unmanageable for humanity and that causes both human and economic losses. At present, and for the benefit of humanity, many investigations and projects are being carried out that aim to mitigate climate change derived from livestock production from a series of activities that aim to face this problem from a multidisciplinary and multifactorial perspective that implies radical changes in ruminant food systems, up to the genetic manipulation of ruminal microorganisms. Based on the above detailed and based on the imperative need to take responsibility for this problem, the present work tries, based on a bibliographic investigation, to put in context the problem of climate change due to the emission of gases from livestock production and describe the activities that are carried out. perform in order to mitigate it.